The relevance of the unique anatomy of the human prefrontal operculum to the emergence of speech - Céline Amiez; Charles Verstraete; Jérôme Sallet; Fadila Hadj-Bouziane; Suliann Ben Hamed; Adrien Meguerditchian; Emmanuel Procyk; Charles R. E. Wilson; Michael Petrides; Chet C. Sherwood; William D. Hopkins (Communications Biology, 2023)
Abstract Identifying the evolutionary origins of human speech remains a topic of intense scientific interest. Here we describe a unique feature of adult human neuroanatomy compared to chimpanzees and other primates that may provide an explanation of changes that occurred to enable the capacity for speech. That feature is the Prefrontal extent of the Frontal Operculum (PFOp) region, which is located in the ventrolateral prefrontal cortex, adjacent and ventromedial to the classical Broca’s area. We also show that, in chimpanzees, individuals with the most human-like PFOp, particularly in the left hemisphere, have greater oro-facial and vocal motor control abilities. This critical discovery, when combined with recent paleontological evidence, suggests that the PFOp is a recently evolved feature of human cortical structure (perhaps limited to the genus Homo) that emerged in response to increasing selection for cognitive and motor functions evident in modern speech abilities.